Correction of metabolic deficiencies in the leukocytes of patients with chronic granulomatous disease - Baehner, Robert L. (1970)
Polymorphonuclear leukocytes from patients with chronic granulomatous disease (CGD) exhibit metabolic and bactericidal deficiencies that may be the result of inadequate production of H(2)O(2). A hydrogen peroxide-generating system was, therefore, inserted into CGD leukocytes. This was accomplished by allowing the cells to phagocytize latex spherules coated with glucose oxidase. This produced an amelioration in the known metabolic deficiencies of these cells during phagocytosis: (a) intracellular (catalatic) formate oxidation dependent upon hydrogen peroxide production was enhanced fourfold; and (b) hexose monophosphate shunt activity, which other workers have shown to be at least partially dependent upon the availability of H(2)O(2), was markedly stimulated. These data strengthen the evidence that the fundamental metabolic lesion in CGD cells during phagocytosis is indeed deficient production of hydrogen peroxide, probably, as previously shown, due to diminished oxidase for reduced nicotinamide adenine dinucleotide.